Research Into The Interaction Of Industrial Tricone Bit`S Buttons With Rock During Drilling - Toshov J.B., Toshniyozov L.G. (International Journal of Advanced Science and Technology, 2020)
Various approaches to the research of the interaction of rock-cutting tools with rock are analyzed in the article. In contrast to analytical and experimental methods with their limited and costly applicability, it is proposed to use numerical modeling to better represent the mechanics of rock destruction, to visualize the stages of destruction in a short time and in a cheaper way. This article allows to get an idea that using the finite element method can get mathematical modeling of plastic deformation, assess the stress-strain state of the bit and optimize the structural elements and working conditions of the rock cutting tool, analyze the dynamics of fracture forces and others. The dynamic interaction of the drill bit with the rock in case of  arrangement of buttons by a producer on one crown is investigated. In the process of analysis, it was found that the interaction of bit inserts with rocks has a force action on the area of the rock in an intensively fluctuating way. The arrangement of the buttons in in industrial tricone bit have only tensile stress in the longitudinal direction, contributing to a coverage of the fracture zone along with the path of buttons on the rock. The use of numerical modeling in the development of rock cutting tools in Drilling and blasting, due to its low cost and laboriousness can effectively reduce the cost of drilling during open pit mining, on top it has been proven to be a reliable method to meet the standards of optimal drill bit design criteria.